Technologies of trauma : cultural formations over time - Ibrahim, Yasmin (Reader in international business and communications) (Emerald Publishing Limited, 2022)
Media technologies do not simply record or represent trauma but transform trauma into a cultural form that is multifariously commodified in different contexts. In this crucial new text, Ibrahim introduces us to the notion of 'technologies of trauma', in deconstructing the idea of trauma as a cultural form in society. Ibrahim examines the trajectory of witnessing and testimony through modernity, utilizing the technologies of trauma as a conceptual lens. Such a notion acknowledges humanity's reliance on technologies to transmute history, trauma, or memory, transforming technologies from medium and machine into artefacts for circulation and exchange. The transcendence of medium into artefacts as sites of trauma equally highlights the socio-political frames within which testimony is extracted and witnessing is enacted, unleashing trauma as a cultural form and a resonant genre of popular consumption. The development of print, photography, television, and digital platforms as technologies of trauma reiterates the popularization of trauma as a cultural genre, witnessing and testimony as cultural forms reiterating how these are intimately implicated in our emergence as active consuming communities of trauma and in tandem how these remake us as vulnerable subjects through the circulation of trauma within a popular consumption economy.